PERAN UNITED NATIONS INTERNATIONAL CHILDREN’S FUND (UNICEF) DALAM MEMENUHI HAK ANAK ETNIS ROHINGYA DI BANGLADESH - Larenza, Descri; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes the role of UNICEF towards Rohingya children in refugee camps in Bangladesh related to violations of children's rights committed by Myanmar. Through this paper, the author describes the background of the conflict between ethnic Rohingya and Myanmar until the crossing to Bangladesh, seeing the number of children who are neglected and in need of help, the international organization UNICEF helps in realizing the rights of ethnic Rohingya children. Some of the roles played by UNICEF to help the Rohingya, especially children, are to show the fulfillment of children's rights such as providing nutrition, health, water, sanitation, child protection and education. This research uses qualitative methods and descriptive analysis. With data collection techniques through literature study sourced from several e-books, e-thesis, journals, reports, websites, and email correspondance. This research uses the perspective of pluralism and the theory of International Organization developed by Clive Archer. The results of this paper indicate what UNICEF (United Nation International Children's Fund) has done to Rohingya ethnic children in refugee camps in Bangladesh. Keywords: UNICEF, Rohingya Ethnic, International Organizations.